Abstracts from The Cold Weather Operations Conference 2021. Issue 1 (31st December 2022) - Norheim, Arne Johan; Rannestad, Bård; Howes, Richard; Rein, Erling Bekkestad; Jørum, Ellen; Friedl, Karl; Havenith, George; Teien, Hilde Kristin; Mercer, James Brian; Melau, Jørgen; de Weerd, Louis; Smith, Michael; et al.
ABSTRACT: A common effort for both military and civil healthcare is to achieve knowledge-based health care in cold weather injuries and fatal accidents in harsh arctic environment. The Cold Weather Operations Conference in November 2021, having more than 300 participants from 20 countries, was addressing the prevention and treatment of injuries and trauma care in cold weather conditions and the challenges for military prehospital casualty care. The intention of the programme was to stimulate further research and systematic knowledge-based clinical work. The abstracts from the conference present cold weather research and clinical experience relevant for readers of the International Journal of Circumpolar Health.